Polar Climate Change as Manifest in Atmospheric Circulation - Screen, JA; Bracegirdle, TJ; Simmonds, I (Current Climate Change Reports, 2018)
This is the author accepted manuscript. The final version is available from Springer via the DOI in this record. Purpose of Review. Dynamic manifestations of climate change, i.e. those related to circulation, are less well understood than are thermodynamic, or temperature-related aspects. However, this knowledge gap is narrowing. We review recent progress in understanding the causes of observed changes in polar tropospheric and stratospheric circulation, and in interpreting climate model projections of their future changes. Recent Findings. Trends in the annular modes reflect the influences of multiple drivers. In the Northern Hemisphere there appears to be a “tug-of-war” between the opposing effects of Arctic near-surface warming and tropical upper tropospheric warming; two predominant features of the atmospheric response to increasing greenhouse gases. Future trends in the Southern Hemisphere largely depend on the competing effects of stratospheric ozone recovery and increasing greenhouse gases. Summary. Human influence on the Antarctic circulation is detectable in the strengthening of the stratospheric polar vortex and the poleward shift of the tropospheric westerly winds. Observed Arctic circulation changes cannot be confidently separated from internal atmospheric variability. James Screen received funding from The Leverhulme Trust (PLP-2015-215) and the Natural Environment Research Council (NERC; Grant NE/N018486/1). Thomas Bracegirdle was funded by NERC, both as part of the British Antarctic Survey Polar Science for Planet Earth Programme and Grant NE/N01829X/1. Parts of this work were made possible by an Australian Research Council grant (DP160101997) to Ian Simmonds and James Screen